Menghadapi Syirik di Zaman Modern : Tanda Tanda dan Cara Menghindarinya - Intan Permata Sari; Tiara Apni Melpa; Andreas Zen (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Shirk, as the biggest sin in Islamic teachings, remains a serious threat even though the modern world is increasingly developing. In this era, shirk not only appears in clear forms such as idol worship, but also in more subtle forms through the worship of certain objects, technology and figures. This journal aims to identify signs of shirk that are developing in modern times and provide solutions for Muslims to avoid it. Using a qualitative-descriptive approach, this research examines various shirk phenomena that can be found in everyday life, such as worship of supernatural objects, a focus on technology, and secular thinking that ignores the role of God in life. Apart from that, this journal also suggests practical steps to avoid shirk, such as strengthening understanding of monotheism, maintaining sincere intentions in worship, and increasing devotion to Allah. The research results show that strengthening monotheism and correct understanding of Islamic teachings is the main key in protecting oneself from the influence of shirk in this modern era.